Identifying and Analyzing Systems Failures: An Interactive, Experiential Learning Approach to Quality Improvement for Clerkship-Level Medical Students - Galina Gheihman; Brent P. Forester; Niraj Sharma; Cynthia So-Armah; Kathleen A. Wittels; Tracey A. Milligan (MedEdPORTAL, 2021)
Introduction Medical students are positioned to observe, document, and explore opportunities to improve patient safety and quality in their institutions. Medical schools are introducing quality improvement (QI) knowledge and skills in the preclinical classrooms, yet few provide opportunities to apply these tools in the clinical setting. Methods Clerkship students participated in two 1-hour sessions, organized in groups of 12–15 students, led by faculty with QI expertise. The sessions in the module introduced core concepts in QI and patient safety, while drawing on students' own clinical experiences. Students identified a system failure they encountered in their own clinical setting/practice and analyzed contributing factors using the 5 Whys Tool. We evaluated the efficacy of the two-session module with a pre- and postsurvey of students' self-reported change in knowledge, skills, and attitudes. Surveys also assessed students' satisfaction with module content and format. Faculty perspectives were solicited by email. Results In April-May 2019, 59 students at a large US medical school participated. Of students, 73% and 53% completed pre- and postsurveys, respectively. All students submitted a report of an identified systems failure and their analysis of contributing factors. Students' self-rated knowledge and skills increased significantly. Students preferred active engagement compared to passive learning. Students and faculty identified areas for future module improvement. Discussion The educational program was well received and increased students' knowledge and confidence in core concepts of QI and safety. The module addressed the requirement for graduating students to identify safety incidents and contribute to a culture of QI.